Kontroversi QadhaÔÇÖ Shalat dalam Pemikiran Ibnu Hazm: Tinjauan Mufassir dan Muhaddis - Massolihin, Edi; SyifaÔÇÖ, Manzilu; as-Shidqi, M. Iqbal; Syafi'ie, A Musta'in (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study examines the differing views of Ibn Hazm al-Andalusi and the majority of Islamic jurists regarding the obligation of making up missed prayers (qadhaÔÇÖ Shalat). This disagreement has caused confusion among Muslims regarding the ruling on qadhaÔÇÖ prayers. The main question is: To what extent can Ibn HazmÔÇÖs argument be justified through Qur'anic exegesis and hadith analysis? This study employs a comparative library research method, examining Ibn HazmÔÇÖs work, particularly Al-Muhalla, and comparing it with authoritative tafsir and relevant hadiths. The analysis reveals that Ibn HazmÔÇÖs interpretation is overly literal, neglecting context and the general principles of Islamic law. Therefore, his claim is considered methodologically weak. Most exegetes and hadith scholars affirm that qadhaÔÇÖ prayer remains obligatory if performed under conditions that align with Shariah law and the principle of ease (taysir).